Peranan Dewan Perwakilan Rakyat dan Keterlibatan Publik dalam Pembentukan Undang Undang tentang Hukum Acara Pidana - Regiska Sukma Budi Wardani; Ervina Firszian; Michael Tobias Reynaldo Wibowo; Akhmal Fahrizi Indrayana; Iqbal Hakim Hasna Mulya (Fakultas Hukum, UPN Veteran Jawa Timur, 2026)
The revision of Indonesia's Criminal Procedure Code (Law No. 8 of 1981, KUHAP) reflects a critical stage in the nation's legal development, where the sovereignty of the people and the principles of a constitutional state must be upheld. This paper investigates the role of the House of Representatives (Dewan Perwakilan Rakyat, DPR) in exercising its legislative authority and examines the extent of public participation in the drafting process. The study aims to evaluate whether the revision embodies democratic legitimacy by balancing procedural compliance with substantive engagement. Using a normative juridical approach enriched by empirical observations of parliamentary debates, civil society critiques, and consultation mechanisms, the analysis reveals that DPR carried out its formal duties of drafting, deliberating, and enacting the bill. However, public involvement remained limited, often symbolic, and insufficiently integrated into the final provisions. These findings highlight a persistent gap between the constitutional ideal of sovereignty residing in the people and the practical realities of legislative processes. The paper concludes that the legitimacy of KUHAP's revision depends not only on DPR's procedural authority but also on strengthening participatory mechanisms to ensure transparency, accountability, and the protection of fundamental rights, thereby aligning with Indonesia's constitutional mandate to advance justice, sovereignty, and public welfare. Keywords: Criminal Procedure Code; DPR; Legislative Process; Public Participation; Democratic Legitimacy.